સાબિત કરો કે : $\cos 6 x=32 x \cos ^{6} x-48 \cos ^{4} x+18 \cos ^{2} x-1$
$L.H.S.$ $=\cos 6 x$
$=\cos 3(2 x)$
$=4 \cos ^{3} 2 x-3 \cos 2 x\left[\cos 3 A=4 \cos ^{3} A-3 \cos A\right]$
$=4\left[\left(2 \cos ^{2} x-1\right)^{3}-3\left(2 \cos ^{2} x-1\right)\right]\left[\cos 2 x=2 \cos ^{2} x-1\right]$
$=4\left[\left(2 \cos ^{2} x\right)^{3}-(1)^{3}-3\left(2 \cos ^{2} x\right)^{2}+3\left(2 \cos ^{2} x\right)\right]-6 \cos ^{2} x+3$
$=4\left[8 \cos ^{6} x-1-12 \cos ^{4} x+6 \cos ^{2} x\right]-6 \cos ^{2} x+3$
$=32 \cos ^{6} x-4-48 \cos ^{4} x+24 \cos ^{2} x-6 \cos ^{2} x+3$
$=32 \cos ^{6} x-48 \cos ^{4} x+18 \cos ^{2} x-1$
$=\operatorname{R.H.S}$
$cos\, \frac{\pi }{{10}} \,cos\, \frac{2\pi }{{10}} \,cos\,\frac{4\pi }{{10}}\, cos\,\frac{8\pi }{{10}}\, cos\,\frac{16\pi }{{10}}$ =
$cos^273^o + cos^247^o + (cos73^o . cos47^o )$ =
$\tan 3A - \tan 2A - \tan A = $
$\frac{{\cos A}}{{1 - \sin A}} = $
$\frac{{\sin 3\theta - \cos 3\theta }}{{\sin \theta + \cos \theta }} + 1 = $